Effect of Na-alginate and bead diameter on lactic acid production from pineapple waste using immobilized Lactobacillus delbrueckii ATCC 9646 - Idris, Ani; Wahidin, Suzana (2005)
Batch fermentation of glucose to lactic acid was performed using immobilized Lactobacillus delbrueckii subsp. Delbrueckii ATCC 9646 under anaerobic condition for 72 hours. Liquid pineapple waste medium was used as the fermentation medium and the effects of Na-alginate concentration and bead diameter on cell growth, glucose consumption and lactic acid production were investigated. The results indicate that Na-alginate and bead diameter have a significant effect on the lactic acid production. The maximum concentrations of lactic acid produced at 56 hours of fermentation were 29.39 g/L at 2.0% Na-alginate concentration and 30.27 g/L for 1.0mm bead diameter with initial glucose concentration of 31.3 g/L. Thus, it is observed that the conversion yields for lactic acid production are 93.8% and 96.7% at 2.0% Na-alginate and 1.0 mm of bead diameter respectively.